(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
The aim of the paper is to analyse the justification for and efficiency of the organisation of a Living Lab within the higher education system as an environment for the development of stimulating tourism ideas and entrepreneurship recommendations. The paper proposes the methodology by means of which the set problem area would be addressed and innovative solutions and recommendations reached for tourism entrepreneurship.For the purposes of identification of the concept elements and research methodology which the “Living Lab”, as an innovative dynamic laboratory implements, quantitative statistics and qualitative methods of creative thinking Brainstorming and Brainwriting are analysed in the paper. Through the Living Lab model, they contribute to the development of creativity and generate quality and innovative ideas and, in accordance with these, establishment of the most efficient model for problem solving in the tourism environment is proposed.The purpose of the paper is to present an innovative model of consideration and evaluation of problems and potential solutions in tourism entrepreneurship. Summarised considerations represent a scientific contribution to the new theory of problem solving and innovations in tourism entrepreneurship. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.